Analisis Metode REBA pada Kegiatan Service Kendaraan Roda Dua di PD. Heran Motor Sport Sukabumi - Mochamad Fathur Al Basyiri; Kusnadi Kusnadi; Dene Herwanto (Peneliti.net, 2022)
Companies in the current Covid-19 pandemic condition still want the productivity of their workers to always increase. Ergonomics problems that are often encountered are in the workplace, especially those related to human strength and endurance in carrying out their work which is often referred to as musculoskeletal disorder. Rapid Entire Body Assessment / REBA is a posture analysis method that can be used quickly to assess work position. From the results of the NBM questionnaire, it can be seen from the average value of complaints from mechanics on body parts which are used as material to be taken into consideration whether later tools will be made or how each mechanic works that must be changed. To determine whether the mechanics work or work position and the need for assistive devices, further processing is required using the REBA (Rapid Entire Body Assessment) method. In the process of applying the REBA method, the activities of each work activity are cut to make it easier to make scores